Reliability Augmentation through Technological Applications in Indian Aircraft Maintenance Training sector - et. al., C.S. Karunakaran , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The paper focuses on the technological needs in Indian aircraft maintenance training sector towards reducing the human errors and to enhance the maintenance reliability. An overview of Indian MRO s’ skill requirements and the immediate necessity to improve the standards in maintenance human factors and technology based training is elaborated. The existing level of Indian AMT training in comparison to international standards are discussed to spot the areas with scope of improvement and the weak link in existing process. Need of maintenance training with intense knowledge and practical exposure can downturn maintenance errors and aid in cutting cost of the maintenance expenditure by increasing reliability were discussed. Impact of Computerised Maintenance Management System (CMMS), in augmenting current maintenance performance and its importance in terms of efficient operation and Labour maintenance were reviewed. Technology identification to address the need for improvement in traditional training, using the applications of Virtual Reality (VR) and Augmented Reality (AR) in maintenance training would equip the Aircraft Maintenance Trainees (AMT’s) with complete knowledge and practice were analysed. This view point can be a thought provoking research to evaluate a right road map for improving the current Indian aircraft maintenance training sector to global standards resulting in optimising the state of India’s MRO self-reliance ability.